IMPLEMENTASI MODEL PEMBELAJARAN PICTURE AND PICTURE DALAM MENINGKATKAN HASIL BELAJAR ANAK USIA DINI - Fathor Rozi; Faizatul Widat; Eka Efandari (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
This study aims to analyze and study the implementation of the picture and picture learning model in improving early childhood learning outcomes. This is done to assist teachers in implementing learning so that early childhood learning outcomes can increase. Researchers used a qualitative approach to the type of case study. This research was conducted at RA Uswatun Hasanah institute. The results showed that RA Uswatun Hasanah school had used the picture and picture learning model in improving the learning outcomes of their students. The implementation of picture and picture learning is carried out in several stages, namely; the first stage is preparation, the second stage is implementation, the third stage is evaluation. Implementation achieved by using the picture and picture method, students are more interested and enthusiastic about participating in learning so that children's learning outcomes increase.